The Athenian against Atheists: Theological Persuasion in Plato’s Laws - Baliukonis, Simonas (Literatūra, 2020)
This paper examines the argument for the existence of gods, formulated by the Athenian in the 10th book of Plato’s Laws. The purpose of this investigation is to find out whether the argument persuades its intended audience – the atheists. The analysis is divided into three parts: 1) the investigation of the Athenian’s concept of persuasion; 2) the examination of the argument’s audience; 3) the reconstruction of the argument and the evaluation of its logical soundness, compliance with the defined criteria of persuasion, and suitability for the defined audience. This paper argues that the Athenian’s argument for the existence of gods should persuade atheists.